2014
DOI: 10.1016/j.jmb.2014.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal MUC2 Mucin Supramolecular Topology by Packing and Release Resting on D3 Domain Assembly

Abstract: MUC2 is the major gel-forming mucin of the colon forming a protective gel barrier organized into an inner stratified and an outer loose layer. The MUC2 N-terminus (D1-D2-D'D3 domains) has a dual function in building a net-like structure by disulfide-bonded trimerization and packing the MUC2 polymer into an N-terminal concatenated polygonal platform with the C-termini extending perpendicularly by pH- and calcium-dependent interactions. We studied the N-terminal D'D3 domain by producing three recombinant variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 32 publications
1
60
2
Order By: Relevance
“…1 (22). More recent structural studies of the MUC2 N-terminal D3 domain suggested that every second MUC2 mucin layer is rotated 180° and the N-terminal ring structures meet (29). Upon secretion, the densely packed mucin expands >1,000-fold into large nets (Fig.…”
Section: Goblet Cell Exocytosismentioning
confidence: 99%
“…1 (22). More recent structural studies of the MUC2 N-terminal D3 domain suggested that every second MUC2 mucin layer is rotated 180° and the N-terminal ring structures meet (29). Upon secretion, the densely packed mucin expands >1,000-fold into large nets (Fig.…”
Section: Goblet Cell Exocytosismentioning
confidence: 99%
“…To carry out these essential functions, gel-forming mucins are cross-linked into extended disulfide-linked architectures. The respiratory mucins form bundles of linear covalent polymers (Thornton et al, 2018), and it was proposed that the intestinal mucins form a stacked hexagonal network (Ambort et al, 2012;Nilsson et al, 2014). The non-mucin molecule VWF, produced by endothelial cells and platelets to function in hemostasis and thrombosis (Springer, 2014), evolved by exploiting aspects of the mucin disulfide-mediated assembly mechanism despite its distinct physiological context ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The secreted mucus is believed to consist of layers of these nets ( Figure 3D). It is important to note the pore size of these nets should be approximately 1 µm [36,[56][57][58].…”
Section: Mucin Polymerizationmentioning
confidence: 99%
“…When inhaled particles or microbes reach the lung they become attached to the mucus gel layer and are cleared from the lungs by the action of the cilia moving the mucus layer up and out of the lungs. MUC2 nets Theoretical 1 µM [36,56,57,64] Pig jejunal mucus Particle tracking Ex vivo scraped mucus from the proximal jejunum 500 nm [20] Pig jejunal mucus Atomic force microscopy Jejunal mucus collected with protease inhibitors. Overnight extraction in 4M guanidinium chloride followed by density gradient purification.…”
Section: The Airway Mucus Barriermentioning
confidence: 99%